(untitled) (Applied Biological Research, 2014)
The seeds of Jatropha curcas were harvested from three maturity stages termed as greenish-yellow (40-45 days after anthesis, DAA), yellow (55- 60 DAA) and brownish-black (65-70 DAA) at fortnightly interval from July to December to assess the effects of collection time and capsule maturity on seed germination. It was observed that seed germination varied significantly with the advancement of collection period and capsule maturity. Maximum germination was recorded in the seeds extracted from yellow capsules both under laboratory (85.8%) and nursery conditions (59.1%). Similarly, the seeds harvested during July, August and September collectionsshowed higher germination percentage. Therefore, harvesting of fruits at yellow stage during rainy season appearsbetterfor thecollection of abundantsuperiorquality seeds.